Ustvarjalnost - proces, oseba in produkt - Opaka, Martina (Psihološka obzorja (Ljubljana), 2008)
There are three viewpoints we can understand creativity from - process, person, and product. Until some time ago the choice of a viewpoint determined the definition of creativity, the research method used, and the interpretation of obtained results. The researchers of today tend to integrate all the three viewpoints. The viewpoints of process and person are the two in vitro approaches to creativity research. The former advocates the experimental and the latter advocates the correlational method. Despite the long tradition of the two approaches there are still new discoveries in these fields which contemporary psychology has to offer. The third approach - the viewpoint of a creative product - is an in vivo approach. It has the longest tradition and today it offers a new paradigm in the understanding of creativity by integrating and supplementing the former two viewpoints. This article is a review of contemporary discoveries about creativity using all three viewpoints. From the viewpoint of creativity as a process it describes cognitive processes in a creative individual and interpersonal processes in a social and cultural setting which is the topic of the social psychology of creativity. From the viewpoint of a creative person it lists his/her attributes from biological foundations to personal characteristics and self activity. The third viewpoint of creativity - the viewpoint of a creative product - uses analysis of real creative achievement and discoveries of the former two viewpoints to explain creativity as a stochastic process far more dependent on combinatorics, probability and luck than assumed before.
Keywords: ustvarjalnost; kognitivni procesi; socialno okolje; osebnost; personality